The The Use of Augmented Reality Diorama Media in Natural and Social Sciences Subjects for Fourth Grade Elementary School - Rahmiati, Devi; Sarwi, Sarwi; Sudarmin, Sudarmin; Cahyono, Adi Nur (Journal La Edusci, 2025)
Fourth-grade elementary students learn Natural and Social Sciences thanks to the pedagogical effects of employing Augmented Reality (AR) diorama media. The study utilizes descriptive qualitative methods to determine how students respond cognitively, conceptually and emotionally to learning environments based on AR technology. The author collected data using interviews combined with observations which involved a descriptive analysis for learner performance alongside participation monitoring. AR dioramas create multi-sensory learning conditions which help students interact directly with contextualized educational content to explore scientific and social phenomena better. The technology improved student motivation and created individualized learning paths at the same time that it supported education practices built on principles of Universal Design for Learning (UDL). The study exposed two main hurdles to implementation: restrictions from technology usage combined with the necessity to properly integrate learning methods. The research findings emphasize that teachers should mediate between students and instructional programs through strategic implementation. The study confirms that thoughtfully implemented AR diorama media functions as an effective transformative tool for educational development by connecting novel methodologies with intentional educational practices.